CONSIDERACIONES ACERCA DE LA CRECIDA HISTÓRICA DE JULIO DEL 2006 Y SUS CONSECUENCIAS EN EL BAJO NEUQUÉN - Maria Elena Chiementon; Verónica G. Cortese (Boletín Geográfico)
In recent years, worldwide, the environmental issues have gained unprecedented importance, including those linked to the use and management of water. Discussion is installed, recognizing the strategic role of water resources and the need to manage watersheds sustainably. This paper analyzes the extraordinary flood in July 2006 with a record level in the Neuquén River. This event which showed the vulnerability of populations located downstream Cerros Colorados dam Complex, currently poses a new and intricate scenario. In order to analyze the events of 2006, we previously performed a brief historical and anecdotal overview of Neuquén more important floods and the means used to control them, consisting in construction of hydraulic engineering works. These were very important in the development of fruit production in the valley by allowing irrigation of lands in production. The extraordinary flood July 2006 raised many questions left. It speaks of the urgent need for new engineering works, when we should think about the possibilityof integrated management of watershed as a unit for planning.